Judicial reputation : a comparative theory - Garoupa, Nuno; Ginsburg, Tom (Chicago : The University of Chicago Press, 2016)
Judges are society's elders and experts, our masters and mediators. We depend on them to dispense justice with integrity, deliberation, and efficiency. Yet judges, as Alexander Hamilton famously noted, lack the power of the purse or the sword. They must rely almost entirely on their reputations to secure compliance with their decisions, obtain resources, and maintain their political influence. In 'Judicial Reputation', Nuno Garoupa and Tom Ginsburg explain how reputation is not only an essential quality of the judiciary as a whole, but also of individual judges.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 22, 2016).
Keywords: Judges; Judicial process -- Public opinion; Judicial ethics; Law; Jurisprudence & general issues; Comparative law; International law; Laws of specific jurisdictions & specific areas of law